Las estrategias didácticas para desarrollar el pensamiento lógico-matemático en niños comprendidos entre 4 a 5 años de edad, de la escuela fiscal de educación básica Alonso de Mercadillo de la ciudad de Loja, período 2017-2018 - Pinzón Maza, Carmen Marilú (2019)
This research thesis includes a study on didactic strategies to develop logical-mathematical thinking in children between 4 and 5 years old, from the Fiscal School of Basic Education Alonso de Mercadillo of the city of Loja, period 2017-2018. To this end, the general objective is to: Determine how didactic strategies allow the development of logical-mathematical thinking in children from 4 to 5 years. The methods used for the collection and analysis of the information were: The scientific, inductive, deductive, descriptive and statistical-synthetic method. The technique that was used to know the problems of the institution was the direct observation with which it was observed that the children did not have a good stimulation of logical-mathematical thinking. The instruments that served to collect the information were: a survey directed to three teachers of Initial Level II of said institution, to know what didactic strategies they use to develop the logical-mathematical thought; and, a list of comparison to a sample of 22 children, which allowed to know the current state of logical-mathematical thinking. From the results obtained it could be observed that 35% present a good stimulation in logical-mathematical thinking, while 15% are in the process of acquiring this learning and 50% do not. So it is concluded that girls need stimulation of logical-mathematical thinking and it is recommended to use didactic strategies that help to improve it and in that way achieve a good cognitive development